2013
DOI: 10.1007/s10517-013-2244-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Alimentary High-Fat Diet on Thiol Disulfide Homeostasis in Rats

Abstract: The effects of high-fat diet on the thiol disulfide homeostasis of rats were evaluated by activities of glutathione redox system functioning in the blood and liver. A short-term (30 days) high-fat diet inhibited activities of glutathione-dependent enzymes. High-fat loading for 90 days promoted the development of a compensatory response of the glutathione redox system and restoration of the thiol disulfide homeostasis. The compensatory processes in the glutathione system failed on day 180 of alimentary loading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
(15 reference statements)
2
4
0
Order By: Relevance
“…The lipid storage function of the liver and the preference of red muscle to use fatty acids as fuel explain these tissue-dependent increases [ 31 , 32 ]. These results agree with those of studies showing that a higher lipid content in feed increases both lipid and protein peroxidation markers from 10 to 90% [ 4 , 6 , 11 ]. Interestingly, the reduced AOPP levels in the HP groups could be correlated with the lower nitrogen fractionation (Δδ 15 N) found in the white muscle of the same fish analyzed in this work [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The lipid storage function of the liver and the preference of red muscle to use fatty acids as fuel explain these tissue-dependent increases [ 31 , 32 ]. These results agree with those of studies showing that a higher lipid content in feed increases both lipid and protein peroxidation markers from 10 to 90% [ 4 , 6 , 11 ]. Interestingly, the reduced AOPP levels in the HP groups could be correlated with the lower nitrogen fractionation (Δδ 15 N) found in the white muscle of the same fish analyzed in this work [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, the opposite results were shown by Lasker et al (2019) [11], who observed that a high-fat diet reduced the activities of SOD and CAT. This is in line with the results observed in murine models by Karaman et al (2013) [6] for reduced thiols and by Jarukamjorn et al (2016) [57] for relative expression and enzyme activity, with an initial upregulation of protective mechanisms that is exceeded and depressed after a while.…”
Section: Effect Of Diet On Oxidative Stress Statussupporting
confidence: 91%
See 1 more Smart Citation
“…Karaman et al [ 30 ] investigated the effects of high fat diet on the thiol-disulfide metabolism of the rats. They found that the compensatory response failed in the glutathione and the impairment of redox imbalance in thiol/disulfide metabolism after 180 days alimentary.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfhydryls are characterized as SH‐ thiol groups that act as antioxidants in the body, such as glutathione and when present in proteins and other compounds can be oxidized in the presence of free radicals (Halliwell & Gutteridge, 2007). Karaman and cols demonstrated that rats submitted to a high‐fat diet presented a recover of glutathione levels at 90 days, but not at 30 or 180 days, as well as an improvement in glutathione reductase (Karaman, Novgorodtseva, & Yan, 2013). In our study, the sulfhydryl content in liver and plasma of treated animals were increased, which it is possible a compensatory response of antioxidant system stimulated by the consumption of fat and cholesterol.…”
Section: Discussionmentioning
confidence: 99%